2000
DOI: 10.1016/s0928-8244(00)00201-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and immunologic characterization of a novel serotype 4, 15 strain of Neisseria meningitidis

Abstract: The porin proteins of Neisseria meningitidis are important components of outer membrane protein (OMP) vaccines. The class 3 porin gene, porB, of a novel serogroup B, serotype 4, 15 isolate from Chile (Ch501) was found to be VR1-4, VR2-15, VR3-15 and VR4-15 by porB variable region (VR) typing. Rabbit immunization studies using outer membrane vesicles revealed immunodominance of individual PorB (class 3) VR epitopes. The predominant anti-Ch501 PorB response was directed to the VR1 epitope. Anti-PorB VR1 mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…It is not clear why we, as others before us (Urwin et al ., ; Bash et al ., ), observed discrepancies in the ability of both mAbs and pAbs to bind the same hybrid PorB type as represented in immunoblots, dot blots and ELISAs. Although all experiments were performed in the presence of the detergent Zwittergent 3–14, it is likely that the insolubility of PorB impacted folding such that rPorB could not fully recapitulate the native structure observed in the context of a bacterial OM.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It is not clear why we, as others before us (Urwin et al ., ; Bash et al ., ), observed discrepancies in the ability of both mAbs and pAbs to bind the same hybrid PorB type as represented in immunoblots, dot blots and ELISAs. Although all experiments were performed in the presence of the detergent Zwittergent 3–14, it is likely that the insolubility of PorB impacted folding such that rPorB could not fully recapitulate the native structure observed in the context of a bacterial OM.…”
Section: Discussionmentioning
confidence: 98%
“…Studies attempting to correlate the binding of mAbs with PorB amino acid sequence have struggled to elucidate the reason that strains exhibiting identical epitope loops do not always bind the same antibodies (Sacchi et al ., ; Urwin et al ., ; Bash et al ., ; Dyet and Martin, ). Ch501, for example, which was originally identified based upon its ability to be bound by both serotype 15 and 4 mAbs in dot blot assays, is bound by an additional serotype 4 mAb (MN14G21.17) that was not tested in these studies (Bash et al ., ) but is believed to be specific for L1 4 (Urwin et al ., ). In contrast, the N150/88 strain, which contains the same porB sequence as BB1350 and an identical L1 4 sequence relative to Ch501, is not bound in the same assay (Bash et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wide diversity of PorA proteins and geographic differences in their prevalence pose major challenges to designing an effective group B vaccine for global use. Studies have shown that antibodies directed against immunodominance variable region of OMPs produced a broader protective immune response (6). Therefore, data on the characteristics of variable region in OMPs are needed in Scotland.…”
mentioning
confidence: 99%